2005
DOI: 10.1038/sj.onc.1208730
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the neuregulin-1/ErbB signaling pathway promotes the proliferation of neoplastic Schwann cells in human malignant peripheral nerve sheath tumors

Abstract: Patients with neurofibromatosis type 1 develop aggressive Schwann cell neoplasms known as malignant peripheral nerve sheath tumors (MPNSTs). Although tumor suppressor gene mutations play an important role in MPNST pathogenesis, it is likely that dysregulated signaling by as yet unidentified growth factors also contributes to the formation of these sarcomas. To test the hypothesis that neuregulin-1 (NRG-1) growth factors promote mitogenesis in MPNSTs, we examined the expression and action of NRG-1 in human MPNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 60 publications
3
74
0
Order By: Relevance
“…In contrast to other erbB family members (EGFR, erbB3, erbB4), erbB2 lacks a ligand-binding domain. ErbB2 must therefore form heterodimers with other family members, all of which were detected in MPNSTs, 15 to respond to growth factors. Application of pan-erbB inhibitors appears tempting to inhibit this cross talk (heterodimerization).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other erbB family members (EGFR, erbB3, erbB4), erbB2 lacks a ligand-binding domain. ErbB2 must therefore form heterodimers with other family members, all of which were detected in MPNSTs, 15 to respond to growth factors. Application of pan-erbB inhibitors appears tempting to inhibit this cross talk (heterodimerization).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is cumulating evidence of a role for EGFR and erbB2 in nerve sheath tumors, 14,15 previous studies did not systematically analyze these potential therapeutic targets in larger panels of human MPNSTs. We therefore studied genetic alterations and expression of erbB2 and EGFR in a set of 37 human MPNSTs and four MPNST cell lines.…”
mentioning
confidence: 98%
“…One of these is NRG1, a growth factor that regulates Schwann cell proliferation, survival, migration, and maturation during development. We have shown that NRG1 and all three of its receptors (the erbB2, erbB3, and erbB4 receptor tyrosine kinases) are co-expressed in human neurofibromas and MPNSTs; the resulting constitutive activation of these receptors drives the proliferation, 92 survival, 93 and migration 94 of human MPNST cells. To determine whether inappropriate activation of the NRG1/erbB signaling is sufficient to induce tumorigenesis, we created transgenic mice in which a secreted NRG1 isoform is overexpressed in Schwann cells (P 0 -GGFb3 mice).…”
Section: Currently Available Mouse Models Of Neurofibroma and Mpnst Pmentioning
confidence: 99%
“…Preclinical studies have demonstrated that blockade of the EGF receptor-related erbB receptors with PD168393 and PD158780 have blocked proliferation of MPNST cells in an in vitro setting. 144 The utility of direct EGF receptor blockade with gefitinib (Iressa) as a potential therapeutic end point for MPNST treatment has also been demonstrated in an in vitro setting. 30 In addition to having been demonstrated in preclinical and clinical studies for the treatment of a wide variety of cancers, 34 EGF receptor blockade has been extended into the clinical context for treatment of MPNSTs.…”
Section: Schwann Cell-specific Approachesmentioning
confidence: 99%